2008
DOI: 10.1007/s12289-008-0154-5
|View full text |Cite
|
Sign up to set email alerts
|

A new approach for toolpath programming in Incremental Sheet Forming

Abstract: International audienceBecause of involved means and process implementation, toolpath generation is a key topic linked to incremental sheet forming. Process characteristics ask for specifically dedicated toolpaths. This paper firstly evaluates the impact of toolpath type and of other programming parameters on process implementation through an experimental campaign performed on a parallel kinematics machine tool. Then, a new approach to perform Intelligent CAM programmed toolpaths is proposed. This innovative to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Result showed that the forming forces were higher in case of profile tool path as compared to those obtained with the helical tool path. Rauch et al [73] evaluated the impact of tool path types and proposed a new approach to perform intelligent CAM program based for the tool path optimization.…”
Section: Materials Typementioning
confidence: 99%
See 4 more Smart Citations
“…Result showed that the forming forces were higher in case of profile tool path as compared to those obtained with the helical tool path. Rauch et al [73] evaluated the impact of tool path types and proposed a new approach to perform intelligent CAM program based for the tool path optimization.…”
Section: Materials Typementioning
confidence: 99%
“…It was found that the predicted forces were in good agreement with the experimental results. Arfa et al [48] studied the influence of sheet thickness on AA3003-O sheets by experimental work and simulation with ABAQUS software with a set of standard Profile [2], [4][5], [30][31], [36][37][38], [56][57][58][59][60][61][62][63][64], [66][67], [69][70][71][72][73], [76][77], [81] Helical [7][8], [23], [32], [41][42][43], [68], [72], [79] Comparison of tool paths [6], [52][53][54][55] 24% (a) (b) Sudden peaks in axial forces were observed between two consecutive layers in profile tool path. In helical tool path, force variation was smooth.…”
Section: Influence Of Sheet Thicknessmentioning
confidence: 99%
See 3 more Smart Citations